2015
DOI: 10.6018/analesps.32.1.186211
|View full text |Cite
|
Sign up to set email alerts
|

Cómo vivir con EPOC: percepción de los pacientes.

Abstract: The aim of this study is to determine the mental model that patients with COPD (chronic obstructive pulmonary disease<strong>)</strong>have about their illness analyzed by the Leventhal´s Common Sense of Self-Regulation Model. An exploratory-descriptive study using qualitative methodology was performed. We included COPD-diagnosed patients attending three urban and a rural primary care centres. We used video-taped group interviews and transcribed them using Atlas.Ti 5.2 program. 22 group interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
2
0
1
Order By: Relevance
“…An interpretative qualitative meta-analysis that had, among others, the objective of exploring the experiences lived by patients in the context of multimorbidity indicated that patients who have structural support may feel isolated if they believe that people in their environment do not want to understand their problems [37]. Additionally, another qualitative study on patients with chronic obstructive pulmonary disease concluded that this sense of incomprehension from their environment can lead people to passively cope with their disease [38]. Items that relate to the need to speak or receive support for aspects beyond the disease were not significantly associated with nonadherence in our study, but this may be due to the social needs and lifelong characteristics of the people who make up the sample.…”
Section: Strengths and Comparison With Other Studiesmentioning
confidence: 99%
“…An interpretative qualitative meta-analysis that had, among others, the objective of exploring the experiences lived by patients in the context of multimorbidity indicated that patients who have structural support may feel isolated if they believe that people in their environment do not want to understand their problems [37]. Additionally, another qualitative study on patients with chronic obstructive pulmonary disease concluded that this sense of incomprehension from their environment can lead people to passively cope with their disease [38]. Items that relate to the need to speak or receive support for aspects beyond the disease were not significantly associated with nonadherence in our study, but this may be due to the social needs and lifelong characteristics of the people who make up the sample.…”
Section: Strengths and Comparison With Other Studiesmentioning
confidence: 99%
“…Beliefs about inhaled treatments are part of a patient's mental representation of COPD. Unlike some chronic diseases, such as cancer [9], AIDS [10], and diabetes [11], for which there are well-defined individual and social mental models, COPD is a rather confusing entity for affected patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Desde el ámbito emocional, los pacientes experimentan ansiedad, temor frente a la muerte, incertidumbre, desesperanza, resignación y, en varias ocasiones episodios depresivos derivados de la limitación física, las hospitalizaciones recurrentes y la pérdida acelerada de la función pulmonar 9 . Por otra parte, en el ámbito social, la pérdida gradual de la autonomía trasforma la relación con su entorno y su familia, e incrementa con ello la dependencia 10 , lo que hace que el cuadro de la enfermedad se convierta en una secuencia de eventos que terminan magnificando el impacto de la EPOC, sobre el desempeño de quienes lo padecen y con ello se deteriore la calidad de vida.…”
Section: Introductionunclassified